Managing demand by using capacity planning for filtermation (MFG) Sdn Bhd / Annuar Musa Shahriman, Khairul Hafiz Mohd Rapi and Mohd Firdaus Alias - Shahriman, Annuar Musa; Mohd Rapi, Khairul Hafiz; Alias, Mohd Firdaus (Arshad Ayub Graduate Business School, Universiti Teknologi MARA, 2018)
This research paper aims to investigate the inability to meet demand by assessing production performance, identifying bottlenecks in the current assembly line process, and discover factors that leads to production efficiency at Filtermation (MFG) Sdn Bhd. Filtermation is a manufacturer for air conditioning and water filtration components located in Banting, Selangor. The company’s production does not able to meet its demand since the past three years. Currently, the plant is using repetitive focus process strategy and most tasks are using manual assembly line and traditional method. In the conceptual framework, this paper has identified three variables in capacity planning, which are manpower flexibility, method and procedures, and equipment that will influence to the efficiency of production and assembly line. Primary data for this study was collected from semi-structured interviews and observation at the company’s production plant. The findings discuss about the production performance, assembly line process, and capacity planning that influence the efficiency of the company. Obviously, all the three capacity planning variables; manpower flexibility, agility in assembly line, and advanced technology and robot utilization influence strongly towards production efficiency. This paper also suggests recommendations on improving efficiency of assembly line and production, for example to modify the current working shifts, and to use more up to date and automated equipment to run tasks in the production floor.